The secret battle of Evan Pao - Shang, Wendy Wan Long (New York : Scholastic Press, 2022)
Evan Pao and his family move to Haddington, Virginia in hopes of keeping his father's notoriety a secret, but a small southern town is not an easy place for a Chinese-American boy to fit in, and one kid, Brady Griggs, seems determined to make things difficult.
Ages 8-12.
Grades 4-6.
Keywords: Chinese American families -- Juvenile fiction; Moving, Household -- Juvenile fiction; Secrecy -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Bullying -- Juvenile fiction; Virginia -- Juvenile fiction